Constructing the Scientific Dialogue in Mathematics: The Search of an Equilibrium between Words and Symbols in Game Theory Research Articles - Lucero Arrua, Graciela Beatriz (2021)
Maestría en Inglés con Orientación en Lingüística Aplicada